2010
DOI: 10.1109/tvlsi.2009.2026047
|View full text |Cite
|
Sign up to set email alerts
|

TABS: Temperature-Aware Layout-Driven Behavioral Synthesis

Abstract: With rising power densities in modern VLSI circuits, thermal effects are becoming important in the design of ICs. Elevated chip temperatures have an adverse impact on performance, reliability, power consumption, and cooling costs. To ensure adequate thermal management, all phases of the design flow must account for thermal effects on their design decisions. We present a two-stage simulated annealing-based high-level synthesis technique that combines power minimization with temperature-aware scheduling, binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thermal effects are another crucial issue in present‐day VLSI circuits due to increasing power densities that lead to elevated on‐chip peak temperatures. Krishnan and Katkoori 31 presented an SA‐based HLS and floorplanning method for energy and temperature‐aware IC designs. The experiments showed that the proposed method could lower peak on‐chip temperatures by 12% on average compared to traditional algorithms that only focus on average power optimization.…”
Section: Related Workmentioning
confidence: 99%
“…Thermal effects are another crucial issue in present‐day VLSI circuits due to increasing power densities that lead to elevated on‐chip peak temperatures. Krishnan and Katkoori 31 presented an SA‐based HLS and floorplanning method for energy and temperature‐aware IC designs. The experiments showed that the proposed method could lower peak on‐chip temperatures by 12% on average compared to traditional algorithms that only focus on average power optimization.…”
Section: Related Workmentioning
confidence: 99%
“…There are no public domain MPSoC programming benchmarks (BM) available for comparative studies. Previously, researchers have extensively used random task graphs generated from computer program [20,[26][27][28][29][30]32]. Consequently, we use task graphs for free [31], to generate a set of four random BMs for this study.…”
Section: Evaluation Frameworkmentioning
confidence: 99%
“…In the work of Krishnan and Katkoori, 9 a two‐stage simulated annealing‐based HLS technique was presented for power minimization with temperature‐aware scheduling and binding. Simulated annealing algorithm creates low‐power solution iteratively and minimizes on‐chip peak temperature by module‐level temperature estimation.…”
Section: Introductionmentioning
confidence: 99%